Efektivitas Pelatihan Menggunakan Moodle Sinkronus Asinkronus Untuk Meningkatkan Pemahaman Implementasi Kurikulum Merdeka Pada Guru SD - Ummu Khairiyah; Lina Eka Retnaningsih; Masruroh Masruroh; Heny Ekawati Haryono (Universitas Sebelas Maret, 2023)
Program Sekolah Penggerak (PSP) is one of the effort made by the government to realize the vision on Indonesian education to become advanced, sovereign, independent, have a personality and create a profile of Pancasila students. Through the driving school program, several activities were carried out, one of which was an online Learning Committee Training (PKP) which was attended by principals and teachers for 10 days using a moodle with an asynchronous synchronous approach. In this study, it will be emphasized whether using a synchronous asynchronous approach is effective in understanding the implementation of an independent curriculum as indicated by the results of the pre-test and post-test. The research subjects used were 18 people consisting of 6 principals and 12 elemetary school teacher from 6 different schools. The result obtained, it was found that the training using the asynchronous synchronous approach was effective in increasing understanding about the implementation of the independent curriculum in elementary schools.